Editorial - Editor IJoLIS (IJoLIS, 2023)
Community engagement is not a new concept, but it has become increasingly important in recent years as libraries strive to remain relevant in an ever-changing landscape. By engaging with community members, libraries can gain valuable insights into the needs, desires, and aspirations of their patrons, and use this information to design and implement services and programs that are tailored to their unique communities.